The Effectiveness of CoComelon Audio-Visual Media on English Vocabulary Learning for Fourth Grade Student at SDN Pulo 1 Ciruas - Robin; Sintawati, Fairus; Dahlina, Ulinuha; Astuti, Peni (JEDLISH : Journal Of Education and English Language Teaching, 2023)
The target of this research is to find out the effect of Teaching Vocabulary by Using CoComelon audio visual media. In this study, the researcher uses experimental research with quantitative approach. The researcher wants to know the effectiveness of CoComelon audio visual media On English Vocabulary Learning for Fourth Grade of SDN Pulo 1 Ciruas. The effectiveness will be knowing the significant differences between the students who are taught without using Audio visual media and those are taught using Audio visual media. In this research, the writer uses a quantitative data analysis technique. The quantitative data of this research is analyzed by using statistical method. Data analysis techniques in quantitative research use statistics. The statistics used in this study are data analysis with descriptive statistics and data analysis with inferential statistics. After statistical calculations a conclusion was obtained that there is a significant effect of CoComelon audio visual learning media on students’ vocabulary learning at fourth grade students of SDN Pulo 1 Ciruas. The result of paired sample between score of pretest and posttest sig. 0.00 < 0.05 (H1 accepted). Thus, it can be said that CoComelon audio visual learning media gave significant effect on students’ vocabulary learning